1995
DOI: 10.2108/zsj.12.457
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Testosterone and Estradiol on Mast Cell Number in the Harderian Gland of the Frog, Rana esculenta

Abstract: The Harderian gland (HG) of the frog Rana esculenta contains mast cells in the interstitial tissue. The mast cell number (MCN) is influenced by sex hormones. Gonadectomy in both sexes provoked a decrease in MCN in January, while no effect was observed in September. Sex hormone-replacement therapy gave different results; estradiol treatment in castrated males and females always increased MCN, while testosterone did not. Acute estradiol treatment provoked an increase in MCN on days 2 and 4 of treatment and the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Indeed, E 2 , upon the binding to its receptors that have been identified also in mast cell, stimulates histamine and serotonin secretion in a dose-dependent manner, while tamoxifen, an antiestrogen, counteracts this action (Vliagoftis et al, 1992). In our previous work, it has been proved that E 2 induces an increase of interstitial connective tissue, together with MCN in the HG of the frog, Pelophylax esculentus (Di Matteo et al, 1995). On the contrary, several experimental data proved that testosterone negatively correlated with MCN (Dias et al, 2022).…”
Section: Resultsmentioning
confidence: 96%
“…Indeed, E 2 , upon the binding to its receptors that have been identified also in mast cell, stimulates histamine and serotonin secretion in a dose-dependent manner, while tamoxifen, an antiestrogen, counteracts this action (Vliagoftis et al, 1992). In our previous work, it has been proved that E 2 induces an increase of interstitial connective tissue, together with MCN in the HG of the frog, Pelophylax esculentus (Di Matteo et al, 1995). On the contrary, several experimental data proved that testosterone negatively correlated with MCN (Dias et al, 2022).…”
Section: Resultsmentioning
confidence: 96%
“…In fact, activation of α‐, β‐, GPr30 receptors for E2 (Xu et al, 2023; Zierau et al, 2012), which have also been identified in mast cells (Nicovani & Rudolph, 2002), stimulates the secretion of histamine and serotonin in a dose‐dependent way; moreover, this action was shown to be counteracted by the antiestrogen tamoxifen (Vliagoftis et al, 1992). Our previous papers reported that E2 induces an increase in interstitial connective tissue along with MCN in the HG of the frog Pelophylax esculentus (Di Matteo et al, 1995). In contrast, several experiments demonstrated that testosterone correlated negatively with MCN (Dias et al, 2022).…”
Section: Resultsmentioning
confidence: 96%
“…Ando et al (1992) found that in the male of Podarcis s. sicula Raf, plasma 17/?-oestradiol is higher in spring and early summer; in this respect, we can speculate that the May peak in MCN found during the annual cycle follows a previous increase in plasma oestradiol. Increased MCN after oestradiol administration was observed in the Harderian gland of both the toad Bufo viridis (Minucci et al, 1994) and the frog Rana esculenta (Di Matteo et al, 1995). In addition in the rat testis, in which mast cells were rarely observed, oestradiol treatment increases MCN, suggesting that oestradiol alters an inhibitory factor for mast cells which is normally present in the interstitium (Gaytan et al, 1986(Gaytan et al, ,1990a.…”
Section: Discussionmentioning
confidence: 98%